1977
DOI: 10.1210/jcem-44-6-1200
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 17α-Hydroxyprogesterone in Spironolactone-Treated Hypertensives

Abstract: When measured by a specific radio-assay method which excludes drug interference, plasma 17alpha-hydroxyprogesterone levels were found to be similar in spironolactone treated hypertensives, in untreated hypertensives, and in normotensive volunteers. No in vivo evidence for a significant inhibitory effect of spironolactone on adrenal 11beta, 17alpha and 21 hydroxylases was uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1978
1978
1980
1980

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(10 reference statements)
0
0
1
Order By: Relevance
“…There are some reports that spironolactone and its major metabolite, canrenone, may interfere with radioimmunoassay for progesterone &YoungLai et al., ), aldosterone (Sadee et al, 1975, and 1 ldeoxycorticosterone (Tan et al, 1975;Abshagen et al, 1977;Tan et al, 1977). In the present study, however, the degree of cross-reactivity of spironolactone, canrenone and potassium canrenoate with our antisera indicated that our radioimmunoassay systems were free from the interference of spironolactone administration.…”
Section: The High-dosage Groupcontrasting
confidence: 50%
“…There are some reports that spironolactone and its major metabolite, canrenone, may interfere with radioimmunoassay for progesterone &YoungLai et al., ), aldosterone (Sadee et al, 1975, and 1 ldeoxycorticosterone (Tan et al, 1975;Abshagen et al, 1977;Tan et al, 1977). In the present study, however, the degree of cross-reactivity of spironolactone, canrenone and potassium canrenoate with our antisera indicated that our radioimmunoassay systems were free from the interference of spironolactone administration.…”
Section: The High-dosage Groupcontrasting
confidence: 50%